2004
DOI: 10.1016/j.molcel.2004.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation of NIP45 Modulates Cytokine Gene Expression in Effector T Lymphocytes

Abstract: Posttranslational modification of proteins within T cell receptor signaling cascades allows T lymphocytes to rapidly initiate an appropriate immune response. Here we report a role for arginine methylation in regulating cytokine gene transcription in the T helper lymphocyte. Inhibition of arginine methylation impaired the expression of several cytokine genes, including the signature type 1 and type 2 helper cytokines, interferon gamma, and interleukin-4. T cell receptor signaling increased expression of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 51 publications
5
123
0
2
Order By: Relevance
“…[Color figure can be viewed in the online issue, which is available at www.interscience.wiley.com.] (Mowen et al, 2004). Methylated NIP-45 heterodimerizes with NFAT and enhances NFAT driven cytokine production upon TCR signaling (Mowen et al, 2004).…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[Color figure can be viewed in the online issue, which is available at www.interscience.wiley.com.] (Mowen et al, 2004). Methylated NIP-45 heterodimerizes with NFAT and enhances NFAT driven cytokine production upon TCR signaling (Mowen et al, 2004).…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…(Mowen et al, 2004). Methylated NIP-45 heterodimerizes with NFAT and enhances NFAT driven cytokine production upon TCR signaling (Mowen et al, 2004). In the case of nuclear receptor HNF4, PRMT1 activates transcription through two mechanisms (Barrero and Malik, 2006).…”
Section: Protein Arginine Methyltransferasesmentioning
confidence: 99%
“…PRMT1, on the one hand, can catalyze the methylation of histones H4 at arginine 3 (H4R3), which acts as a part of the histone code to regulate gene expression (11)(12)(13); on the other hand, recent studies have revealed that a plethora of proteins with methylated arginine residues catalyzed by PRMT1 implicate in a variety of cellular processes. For example, PRMT1 enhances gene transcription by methylating N-terminal arginine residues in NFAT-interacting protein 45, which heterodimerizes with NFAT and then enhances NFAT, driving cytokine production upon TCR signaling of T cells (14,15).…”
mentioning
confidence: 99%
“…In general, methylation of the arginine residue is thought to regulate protein-protein and protein-nucleic acid interactions potentially by increasing its ''hydrophobic'' character (Boisvert et al 2005). Methylation of arginine residues occurs also in other chromatin proteins involved in cytokine signaling, like the PRMT1-driven methylation of the arginine-glycine rich N terminus of the coactivator NIP45, which promotes the association between NIP45 and the transcription factor NFAT and results in an augmented activity of the IL-4 and IFNg gene promoter (Mowen et al 2004).…”
Section: Discussionmentioning
confidence: 99%